Zn(II)/Cd(II) based coordination polymers synthesized from a semi-flexible dicarboxylate ligand and their emission studies. (24th November 2015) - Gupta, Mayank; Ahmad, Musheer; Singh, Ruchi; Mishra, Rupali; Sahu, Jhasaketan; Gupta, Anoop K.
Graphical abstract: Three new coordination polymers have been synthesized using a semi-flexible dicarboxylic acid ligand under hydro(solvo)thermal conditions. They represent homometallic clusters with SBUs varying from dimeric to tetrameric, and show diverse topological architectures. Solid-state luminescence studies of complexes1 –3 have also been carried out at room temperature. Abstract: Three new coordination polymers (CPs) of Zn(II)/Cd(II) have been synthesized using a dicarboxylate ligand, H2 L = 5-(benzylamino)isophthalic acid, under hydro(solvo)thermal conditions. This ligand readily reacts with Zn(II) and Cd(II) metal salts to afford three CPs, [Zn8 (L)6 ( μ 3 -OH)4 (H2 O)6 ]·(DMF)·(H2 O)2.5 n (1 ), [Zn(L)] n (2 ) and [Cd(L)(DMF)] n (3 ). All the complexes have been characterized by single crystal X-ray crystallography (XRD), IR spectroscopy, elemental analysis, thermogravimetry (TGA) and X-ray powder diffraction (PXRD). Single crystal X-ray studies reveal that1 –3 contain homometallic clusters, with SBUs varying from dimeric to tetrameric, depending upon the metal salts as well as the reaction conditions. Topologically, 1 represents an sql net, whereas2 and3 exhibits rare ptr and fes topological nets respectively. Luminescence studies were also carried for complexes1 –3, which exhibit emissions as a pair of bands upon excitation at 405 nm.